2011
DOI: 10.1111/j.1399-0004.2011.01804.x
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis mutations for p.F508del compound heterozygotes predict sweat chloride levels and pancreatic sufficiency

Abstract: Cystic fibrosis (CF) is a monogenetic disease with a complex phenotype. Over 1500 mutations in the CFTR gene have been identified; however, the p.F508del mutation is most common. There has been limited correlation between the CFTR mutation genotype and the disease phenotypes. We evaluated the non-p.F508del mutation of 108 p.F508del compound heterozygotes using the biological classification method, Grantham and Sorting Intolerant from Tolerant (SIFT) scores to assess whether these scoring systems correlated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
3
14
1
Order By: Relevance
“…Sweat chloride was significantly increased in healthy smokers, smokers with COPD, and former smokers with COPD, indicative of reduced CFTR activity in the sweat gland, a site remote from the airway ( Figure 1A). Increased sweat chloride was not accounted for by differences in serum chloride, sodium, or aldosterone (Table 1), and sweat chloride in normal control subjects was similar to that in prior publications (see Figure 1B) (19)(20)(21). Based on the genotypephenotype correlation in CF relating CFTR activity measured by NPD and sweat chloride analysis (22) (Figure 1B), the increase in sweat chloride in COPD subjects is equivalent to a 42% decrement in CFTR function ( Figure 1C) and similar to that observed in the airway (11).…”
Section: Systemic Cftr Dysfunction In Cigarette Smokerssupporting
confidence: 62%
“…Sweat chloride was significantly increased in healthy smokers, smokers with COPD, and former smokers with COPD, indicative of reduced CFTR activity in the sweat gland, a site remote from the airway ( Figure 1A). Increased sweat chloride was not accounted for by differences in serum chloride, sodium, or aldosterone (Table 1), and sweat chloride in normal control subjects was similar to that in prior publications (see Figure 1B) (19)(20)(21). Based on the genotypephenotype correlation in CF relating CFTR activity measured by NPD and sweat chloride analysis (22) (Figure 1B), the increase in sweat chloride in COPD subjects is equivalent to a 42% decrement in CFTR function ( Figure 1C) and similar to that observed in the airway (11).…”
Section: Systemic Cftr Dysfunction In Cigarette Smokerssupporting
confidence: 62%
“…They also showed that patients with a severe CFTR genotype or who were F508del homozygous had higher percentages of malnutrition in comparison to patients with mild genotypes . The finding that a milder genotype is associated with less Pseudomonas colonization lends support to an association between genotype and overweight/obesity. Pedreira et al .…”
Section: Discussionmentioning
confidence: 91%
“…More severe CFTR mutations were found to be associated with higher sweat chloride levels, pancreatic insufficiency, and increased risk of Pseudomonas infection, but neither CFTR genotype nor sweat chloride concentration were significant predictors of FEV 1 % predicted [17,18].…”
Section: Discussionmentioning
confidence: 91%
“…Sweat chloride concentration has been proposed as a measure of the level of CFTR expression, although attempts to directly correlate sweat chloride concentration with clinical phenotypes have not shown consistent results [15][16][17][18]. The reasons for these differing results may be due to study design and varying degrees of power to detect a true association in different studies.…”
Section: Introductionmentioning
confidence: 88%